The conjoint quest for a liberal positive program: "Old Chicago", Freiburg and Hayek - Ekkehard Köhler; Stefan Kolev (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2011)
James M. Buchanan's latest contribution to the post-crisis debate in political economy underpins the necessity to reexamine the legacy of the Old Chicago School of thought, being urged by Buchanan's recently stressed plea at the 2009 Regional Meeting of the Mont Pèlerin Society and at the Summer Institute for the Preservation of the History of Economic Thought in 2010. The focus of the current paper is to follow his plea by exploring the central topoi of the 1930's debate of the Chicago School as seen from the work of Henry Simons and discuss its impact on the academic arena on both sides of the Atlantic thereafter. With respect to this impact, we highlight Friedrich A. von Hayek as the focal scholar who possibly transmits these topoi that later influenced the rise of Freiburgean ordoliberalism in Germany from the mid-1930's onwards as youngest archival findings suggest. By revisiting the MPS 1947 first meeting's minutes and papers, we stress the proximity in mind of Old Chicago, Hayek and the Freiburg School ordo-liberals by contributing an explanation for the surprisingly homogenous direction of these yet unconnected schools of thought. n a next, enhanced version of this project, we will subsequently re-discuss the intellectual origins of Constitutional Political Economy's research program. Following Viktor Vanberg, we argue that CPE can be interpreted as a modernized perspective on economics that carries forward three strands of transatlantic liberal programs, being precisely Old Chicago, Freiburg and Hayek.
Keywords: 330